Back Cover: Supramolecular Assembly of Bis(benzimidazole)pyridine: An Extended Anisotropic Ligand For Highly Birefringent Materials (Chem. Eur. J. 49/2013). Issue 49 (2nd December 2013) - Thompson, John R.; Ovens, Jeffrey S.; Williams, Vance E.; Leznoff, Daniel B.
<x xml:space="preserve">Abstract</x> A series of bis(benzimidazole)pyridine (BBP)‐containing compounds have been synthesized and structurally characterized. Their birefringence values (Δn) were determined, ranging from Δn=0.08(1) to a very high 0.69(3), illustrating the effect on the measurable birefringence of the crystal quality, growth direction and structural alignment of the anisotropic BBP building blocks as described by V. E. Williams, D. B. Leznoff et al. in their Full Paper on page 16572 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>